Incidence of Stroke in People With Diabetes Compared to Those Without Diabetes: A Systematic Review - Kvitkina, Tatjana; Narres, Maria; Claessen, Heiner; Metzendorf, Maria-Inti; Richter, Bernd; Icks, Andrea (Experimental and Clinical Endocrinology & Diabetes, 2023)
Background One of the goals of the St. Vincent Declaration was to reduce serious complications of diabetes, including strokes. However, it remains uncertain whether this goal has been achieved. Study aim: To evaluate the incidence of stroke in the diabetic population and its differences regarding sex, ethnicity, age, and region, to compare the incidence rate in people with and without diabetes, and to investigate time trends.Materials and methods A systematic review was conducted according to the guidelines for meta-analysis of observational studies in epidemiology (the MOOSE group) and the PRISMA group guidelines.Results Nineteen of the 6.470 studies retrieved were included in the analysis. The incidence of stroke in the population with diabetes ranged from 238 per 100,000 person-years in Germany in 2014 to 1191 during the 1990s in the United Kingdom. The relative risk comparing people with diabetes to those without diabetes varied between 1.0 and 2.84 for total stroke, 1.0 and 3.7 for ischemic stroke, and 0.68 and 1.6 for hemorrhagic stroke. Differences between fatal and non-fatal stroke were significant, depending on the time period and the population. We found decreasing time trends in people with diabetes and stable incidence rates of stroke over time in people without diabetes.Conclusion The considerable differences between results can partly be explained by differences in study designs, statistical methods, definitions of stroke, and methods used to identify patients with diabetes. The lack of evidence arising from these differences ought to be rectified by new studies.
Keywords: diabetes; population-based study; incidences; stroke; systematic review